Desertion : a novel - Gurnah, Abdulrazak, 1948- (New York : Riverhead Books, 2005)
"A masterwork by the 2021 Nobel Prize winner in Literature, in which the consequences of an illicit love affair reverberate from the heyday of the British empire to the aftermath of African independence"--
Keywords: English fiction